2018
DOI: 10.1002/ird.2301
|View full text |Cite
|
Sign up to set email alerts
|

Perspective of Water Distribution Based on the Performance of Hydraulic Structures in the Varamin Irrigation Scheme (Iran)

Abstract: Despite the extensive application of check and offtake structures in irrigation canals, their periodic assessment is generally not included in water management plans, especially in Iran. This issue would be more important when there are many problems in water distribution in irrigation projects. In this study the performance and operating status of different hydraulic structures in the Varamin irrigation scheme were evaluated using a precise flowmeter. Results show that Neyrpic modules have an error in range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The resulting water allocation simulation RIBASIM model is configured without considering the water intake from other water resources (e.g., groundwater) and hydrological loss (e.g., infiltration and evapotranspiration) and delivery loss, which make a significant contribution to irrigation water supply [16,18,36,37], especially in the drought season. Thus, the above hydrological variables would be taken in account in the model development.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting water allocation simulation RIBASIM model is configured without considering the water intake from other water resources (e.g., groundwater) and hydrological loss (e.g., infiltration and evapotranspiration) and delivery loss, which make a significant contribution to irrigation water supply [16,18,36,37], especially in the drought season. Thus, the above hydrological variables would be taken in account in the model development.…”
Section: Discussionmentioning
confidence: 99%
“…They found that irrigation delivery service was excellent due to timely physical rehabilitation of the irrigation network. Mohammadi et al [9] conducted an assessment of Varamin irrigation scheme in Iran. The results of their research showed that most of the structures were poorly being operated, leading to unfair delivery and wastage of much water during water distribution.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Total project efficiency includes conveyance, distribution and field application efficiency as defined by Bos & Nugteren (1990). During the comprehensive evaluation, Varamin Irrigation scheme (Iran) was evaluated in terms of distribution (Mohammadi et al 2018) and conveyance efficiency (Mohammadi et al 2019). The results showed that the use of old equipment and poor management of operation and maintenance, caused a decrease in productivity.…”
Section: Introductionmentioning
confidence: 99%